Development of an Injury Indicator Tool to Support Policy and Practice across Wales. - Turner, Samantha L; Lyons, Jane; Lyons, Ronan A (International Journal of Population Data Science, 2019)
Background with rationale Injury is a leading cause of premature mortality, morbidity and disability worldwide. In Wales, injuries result in approximately 3 deaths, 107 hospital admissions and 868 emergency department (ED) attendances every day. Health indicators are quantifiable measures designed to summarise a population’s health, and ultimately inform policy and practice. In 2017, several experts identified a need for injury indicators in Wales, to support injury surveillance and prevention efforts. Main Aim To develop a suite of injury indicators, accessible to the public via an online tool, to inform policy and practice across Wales. Methods/Approach Injury specialists in the All Wales Injury Surveillance System (AWISS) proposed a list of measurable injury indicators, based on: data availability, major areas of interest from a Welsh Government strategy perspective, injuries contributing the greatest burden, and injuries for which effective interventions existed. A consultation process with experts and stakeholders resulted in 25 agreed indicators covering all-cause injuries, falls in older adults, hip fractures, road traffic injuries, injuries in the home and at leisure, burns and scalds, poisonings and intentional injuries. Anonymised, routinely collected ED data, inpatient and mortality data in the Secure Anonymised Information Linkage (SAIL) databank at Swansea University were used to generate indicator estimates. Estimates will be updated annually and are accessible via an online interactive tool. Results The development of a free, online injury indicator tool provides practitioners and policy makers across Wales, with the information required to make informed decisions. However, data quality issues hamper the extent to which conclusions can be made. Conclusions Injury indicators have the potential to inform policy and practice across Wales. The adoption of a simplified, standardised data collection system in EDs across Wales is recommended to improve data validity and reliability.